Water-Electrolytic and Acid-Base Balance in Critically Ill Patients - L. V. Gerasimov (Obŝaâ Reanimatologiâ, 2008)
The review deals with some aspects of correction of water-electrolytic and acid-base balance and this problem-associated infusion therapy. It characterizes various electrolytic solutions and considers the efficacy and safety of their use in terms of homeostatic maintenance. Key words: homeostasis, dyshidria, acid-base balance, acidosis, infusion therapy, crystalloid solutions.